Analysis of the Altilis Cookies Startup Business Method Using the Canvas Model as a Business Development Effort to Provide Gluten and Casein Free Snacks for Autistic Children - Salsabila, Haura Annisaa; Firdausi, Kiyoko Kylanisa Razzaq; Marsindi, Marsindi; Al Fora, Junita; Muliawan, Mohammad Fariz Rizki; Putri, Dias Pratami (Gastronomy Tourism Journal, 2021)
Culinary advancement is increasing year after year. This development is consistent with the rise of pioneering culinary businesses. This culinary development occurs not only in general but also in the development of special foods for autism. Altilis cookies is a startup that sells GFCF (Gluten Free Casein Free) snacks made with breadfruit flour as the main ingredient. Altilis cookies , as a new company, requires a helpful business model analysis to serve as a benchmark for future growth. Using a business approach, the canvas model can build and develop a business that can be created, given, and doubled in value by utilizing the nine existing blocks (Narto, 2017:105). The research method used in this journal is quantitative descriptive. Primary and secondary sources are used to collect data. The purposive sampling method is used to determine informants, which is the technique of deciding informants based on the subjective considerations of researchers (Sugiyono, 2012). The application of this canvas business model is intended to facilitate the business development process because it contains elements with attachments, which are, of course, critical for business progress.